The Detection of straight and Slant Wood Fiber Through slop angle fiber feature - Ratri Dwi Atmaja; Erwin Susanto; Junartho Halomoan; Gurnita Koncara Indraloka; Muhammad Ary Murti (Institute of Advanced Engineering and Science, 2015)
Quality control is one of important process that can not be avoided in industry. Image processing technique is required to distinguish the quality of wood. If it can be done automatically by the computer, it will be very helpful. This paper discusses the detection of straight and slant wood fiber to distinguish it’s quality. This paper propose an algorithm by using only two features i.e. mean (average value of slop angle fiber) and maximumangle (the maximum value of slop angle fiber). Then the classification method is used by tresholding. The result shows the performance is achieved on accuracy 79.2%. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7725